From doubly labelled water to half-life; validating radio-isotopic rubidium turnover to measure metabolism in small vertebrates - Tomlinson, Sean; Maloney, Shane K.; Withers, Philip C.; Voigt, Christian C.; Cruz-Neto, Ariovaldo P. [UNESP] (Wiley, 2013)
The doubly labelled water method (DLW) is widely used to measure field metabolic rate (FMR), but it has some limitations. Here, we validate an innovative technique for measuring FMR by comparing the turnover of isotopic rubidium (86Rb kb) with DLW depletion and the rate of CO2 production (V·co2) measured by flow-through respirometry (FTR) for two dunnart species (Marsupialia: Dasyuridae), Sminthopsis macroura (17 g) and Sminthopsis ooldea (10 g). The rate of metabolism as assessed by V·co2 (FTR) and 86Rb kb was significantly correlated for both species (S. macroura, r2 = 0·81, P = 1·19 × 10-5; S. ooldea, r2 = 0·63, P = 3·84 × 10-4), as was V·co2 from FTR and DLW for S. macroura (r2 = 0·43, P = 0·039), but not for S. ooldea (r2 = 0·29, P = 0·168). There was no relationship between V·co2 from DLW and 86Rb kb for either species (S. macroura r2 = 0·22, P = 0·169; S. ooldea r2 = 0·21, P = 0·253). We conclude that 86Rb kb provided useful estimates of metabolic rate for dunnarts. Meta-analysis provided different linear relationships between V·co2 and 86Rb kb for endotherms and ectotherms, suggesting different proportionalities between metabolic rate and 86Rb kb for different taxa. Understanding the mechanistic basis for this correlation might provide useful insights into the cause of these taxonomic differences in the proportionality. At present, it is essential that the relationship between metabolic rate and 86Rb kb be validated for each taxon of interest. The advantages of the 86Rb technique over DLW include lower equipment requirements and technical expertise, and the longer time span over which measurements can be made. The 86Rb method might be particularly useful for estimating FMR of groups for which the assumptions of the DLW technique are compromised (e.g. amphibians, diving species and fossorial species), and groups that are practically challenging for DLW studies (e.g. insects). © 2013 British Ecological Society.
Keywords: 86Rb kb; Doubly labelled water; Field metabolic rate; Radioisotope turnover; Sminthopsis